Dimensions of Fiber and Jabon Wood Fiber Derivative Value (Anthocephalus cadamba [Roxb] Miq.) in Sialang Dharmasraya and Tabing Padang Regions - Adillah Syafitri; Vauzia Vauzia; Des M (UNIVERSITAS NEGERI PADANG, 2019)
Jabon (Anthocephalus cadamba [Roxb] Miq.) Is a type of wood that is fast growing and has adaptability in various habitat types. Anatomical characteristics of wood are strongly influenced by environmental factors. This study looked at the dimensions of fiber and the derivative value of jabon wood fiber from the Sialang Dharmasraya and Tabing Padang regions. This research is a descriptive research. Observation of fiber dimensions using wood maceration techniques following the Forest Products Laboratory Method. The results showed that the value of wood fiber dimensions from the Sialang area was higher than those from the Tabing area. In Sialang it has wood fiber length of 603.82-1061.23µm, fiber diameter of 12.37-21.22µm, lumen diameter of 3.81-12.97µm, and wall thickness of 2.75-7.49µm. Whereas, in the Tabing area it has wood fiber length of 592.91-844.38µm, fiber diameter 11.80-20.35µm, lumen diameter 6.14-14.35m, and wall thickness of 1.91-4.54µm. The derivative value of jabon Tabing wood fiber is higher (runkel ratio 0.63-0.62, felting power 41.49-50.25, flexibility ratio 0.70-0.52, coefficient of rigidity 0.22-0.16 and mulsteph ratio 50.27-72.92%) compared to Sialang area (runkel ratio 1.15-1.44, felting power 50.01-48.81, flexibility ratio 0.61-0.30, coefficient of rigidity 0.35-0.22, and mulsteph ratio 62.64 to 90.51%). The quality value of jabon wood fiber at Tabing is better than Sialang. The results of this study can be used as information in jabon wood cultivation.